Attribution of Evapotranspiration Changes in Humid Regions of China from 1982 to 2016. Issue 13 (24th June 2020) - Zhang, Dan; Liu, Xiaomang; Zhang, Lu; Zhang, Qi; Gan, Rong; Li, Xianghu
Abstract: This study quantifies the influences of climate variation and vegetation greening on the changes in evapotranspiration ( ET ) over 110 humid catchments of China from 1982 to 2016. A process‐based model considering climate and vegetation changes is employed to estimate ET . The simulated ET compared well with the observed values based on the flux measurements and water balance equation, with the coefficients of determination above 0.62. During the study period, environmental change of the study area was characterized by the increases in air temperature and leaf area index, that is, climate warming and vegetation greening. Annual ET increased at 104 catchments with the trends ranging from 0.01 to 6.2 mm yr −2 . The numerical experiment approach and sensitivity method are used to attribute ET changes to climate variation and vegetation greening. The results show that the contributions of climate variation to ET changes estimated by the two methods are 90.6% and 91.3%, respectively, whereas the contributions of vegetation greening to ET changes are only 9.4% and 8.7%, indicating that climate variation controls ET changes in the study area. However, vegetation greening alters the proportions of ET components, which contributes 59.0%–62.0% to the increase in the ratio of transpiration to ET . This study quantifies the roles of climate and vegetation changes in the dynamics of ET, suggesting that more concerns should be paid on the interactions between ecological processes and hydrological cycle in humid regions. Key Points: Evapotranspiration changes are attributed to climate variation and vegetation greening over 110 humid catchments in China Climate variation controls the dynamics of evapotranspiration over the humid region Vegetation greening has limited influences on evapotranspiration but mainly alters evapotranspiration partitioning